Моделі, методи та інформаційні технології інтелектуального аналізу бізнес-процесів - Манєва, Росіца Іліянова (Національний технічний університет "Харківський політехнічний інститут", 2021)
Дисертація на здобуття наукового ступеня кандидата технічних наук за спеціальністю 05.13.06 – інформаційні технології. – Національний технічний університет "Харківський політехнічний інститут", Харків, 2021. У дисертаційній роботі вирішена актуальна науково-практична задача створення інформаційної технології інтелектуального аналізу бізнес-процесів в умовах неконтрольованих змін зовнішнього середовища. Проведено аналіз систем підтримки прийняття рішень при формуванні організаційної структури робіт, досліджено особливості електронного бізнесу, який характеризується розподіленою системою замовників та виконавців, які спілкуються за допомогою віртуальних каналів, що обумовлює специфіку вирішення задачі. Запропоновано комплексний підхід до аналізу бізнес-процесів на основі багатоагентної моделі. Розроблено метод формування організаційної структури робіт в умовах неконтрольованих змін зовнішнього середовища за рахунок реалізації ситуативно-сценарного підходу та формалізації інтелектуальних процесів прийняття рішень. Проведено аналіз особливостей проектування багатоагентних програмних систем. Розроблено інформаційну технологію інтелектуального аналізу бізнес-процесів за рахунок використання імітаційної багатоагентної моделі та методу відображення поточного стану ситуації у продукційній базі знань, що дозволяє забезпечити ефективність функціонування підприємства в умовах динамічного зовнішнього середовища. Розроблено прототип агентної платформи, заснованої на використанні формальних методів для проектування багатопотокових систем. Проведено апробацію розроблених моделей, підходів та інформаційної технології.

The dissertation for a candidate degree in technical sciences, specialty 05.13.06 – Information Technologies. – National Technical University «Kharkiv Polytechnic Institute», Kharkiv, 2021. The dissertation is devoted to the solution of an important scientific and practical problem of ensuring the efficiency of enterprises in the conditions of uncontrolled changes in the external environment through the development and use of intelligent information technologies on the basis of situational and scenario models. Process mining is to identify, study the effectiveness and optimization of business processes. Process analysis aims to build and improve models of functioning of interacting physical or information objects based on the processing of information that captures such behavior. The need to automate the implementation of business processes (BP) has led to close interaction between business and information technology. The thesis sets the task of ensuring the efficiency of the enterprise in the conditions of uncontrolled changes in the external environment, which consists of the following stages: 1) development of a conceptual model of a flexible PSU in a distributed virtual environment; 2) development of a model of interaction between customers and performers on the basis of situational-scenario approach; 3) development of a mathematical model of flexible BP control; 4) development of a method of formation of organizational structure of performance of works; 5) development of a method of forming an adaptive team of performers; 6) development of applied bases of construction of multi-agent system as a basis of information technology of intellectual analysis of BP. The work proposes a verbal model of analysis of flexible PSUs that operate in dynamic business environments; developed a set of conceptual models of management and representation of flexible PSUs; a formal model of the agent system is proposed on the basis of simulation modeling of the interaction of agents of needs and agents of capabilities, which allows to analyze and promptly reorganize the BP in accordance with changes in the internal or external environment; the FIPA standard is defined as a basis for designing the architecture of the agent platform; an approach based on the description of product rules in the language of finite predicate algebra is proposed to represent the situations that arise during the execution of BP. The research shows that simulation is an effective tool for BP analysis. The analysis of mathematical means of representation of objects of the subject area of the analysis of business processes is carried out. The paper develops a method of information identification to support decision-making based on the use of the apparatus of algebra of finite predicates. The current state of the PSU and possible situations in accordance with alternative BP management solutions are described with the help of the FPA language. The agent platform is an basic tool for developing intelligent multi-agent systems that allows you to create, destroy, interpret, run and move agents. The paper proposes the use of FIPA standards, which provide basic definitions of agent communication concepts. The formal model of the agent proposed in the work is used to build a model of interaction of two types of agents: agents of needs and agents of capabilities. It is shown that the simulation model of interaction of agents of needs and agents of opportunities allows to build a model of management of flexible BP on the basis of the situational-scenario approach. The method of formation of organizational structure of performance of works in the conditions of the dynamic environment is developed. The situational-scenario model of BP management for the decision of a problem of formation and reorganization of organizational structure of performance of works taking into account the data received in real time is developed. Conceptual bases of creation of specialized information technology of intellectual analysis of BP are offered. When building an organizational structure, it is often necessary to evaluate and analyze the existing management structure. For these purposes, the model of management structure analysis is proposed in the work. The method of forming the organizational structure of work to support decision-making in a dynamic environment through the implementation of situational-scenario approach and formalization of intelligent decision-making processes based on the agent model, which allows to adapt the process to current data and uncontrolled changes in the environment. The models and methods developed in the work, aimed at the analysis and formation of a flexible organizational structure of works, are the basis of information technology. A prototype of an agent platform for the implementation of the BP management and analysis model based on the use of formal methods for designing multithreaded systems has been developed. An object-oriented Java programming language, the statically typed Kotlin programming language, was chosen to implement the agent platform prototype. The implementation of the software system prototype is considered for the next problem statement. There are two types of roles in the BP: the customer and the contractor. Multi-agent communication system of customers and contractors allows adding the contractor to change the current state and reorganize the structure of work through the implementation of the functionality of "negotiations". To evaluate the prototype agent platform such parameters as the amount of allocated RAM, the amount of CPU load and the number of allocated threads are estimated. The results show that even with two billion agents created, CPU usage averaged about 34% and maximum CPU usage was 65%. This confirms the assumptions about the effectiveness of the multi-agent system architecture based on the use of the Kotlin-coroutines co-development package. The information technology of intellectual analysis of business processes improves and complements the existing approach to the management of BP and does not contradict the existing practice, which indicates its practical value and validity of use. Approbation of the developed models, approaches and information technology was carried out.
Models, methods and information technologies for intelligent analysis of business processes
Keywords: автореферат дисертації; інформаційна технологія; бізнес-процес; математична модель; метод формування організаційної структури робіт; information technology; business process; mathematical model; method of forming the organizational structure of works; 004.896:510.635